2011
DOI: 10.1097/ccm.0b013e3182227e4a
|View full text |Cite
|
Sign up to set email alerts
|

Simvastatin in traumatic brain injury: Effect on brain edema mechanisms

Abstract: Simvastatin could be a new therapy for reducing posttraumatic edema by preventing damage to tight junctions and neutrophil infiltration into the parenchyma, thus preserving blood-brain barrier integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 48 publications
1
22
0
1
Order By: Relevance
“…4,5 ICAM-1, typically expressed on vascular and immune system cells, induced proinflammatory effects, such as amplifying leukocyte recruitment signals and enhancing neutrophil infiltration into the brain, which exacerbates the brain injury in ICH models. 6,7,21 The main function of VSMCs is to regulate tissue perfusion through graded contraction. Importantly, VSMC display a remarkable plasticity by converting among different phenotypes during some pathologies, a process referred to as VSMC phenotypic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 ICAM-1, typically expressed on vascular and immune system cells, induced proinflammatory effects, such as amplifying leukocyte recruitment signals and enhancing neutrophil infiltration into the brain, which exacerbates the brain injury in ICH models. 6,7,21 The main function of VSMCs is to regulate tissue perfusion through graded contraction. Importantly, VSMC display a remarkable plasticity by converting among different phenotypes during some pathologies, a process referred to as VSMC phenotypic transformation.…”
Section: Discussionmentioning
confidence: 99%
“…These effects are associated with EC barrier protection conferred by simvastatin and mediated by differential Rho GTPase activation (2), inhibition of superoxide generation via reduced nicotinamide adenine dinucleotide phosphate oxidase (3), and the upregulation of integrin-b4 (2). However, circumstantial evidence of a role for claudin-5 in ALI protection by statins is suggested by increased expression of EC claudin-5 in response to statin treatment (7,29). Moreover, a functional link between statins and claudin-5 is suggested by statin regulation of integrin-b1 (30,31), which has been identified as a mediator of increased vascular permeability via effects on claudin-5 (32).…”
Section: Discussionmentioning
confidence: 99%
“…Animal models of TBI have shown that statin therapy may reduce posttraumatic brain edema by preserving blood brain barrier function, preventing damage to tight junctions, and reducing neutrophil infiltration into the brain parenchyma [71]. Simvastatin therapy in a murine model of TBI expressing human beta-amyloid peptide has been shown to blunt TBI-induced increases in beta-amyloid peptide, while reducing hippocampal tissue damage and microglial activation, thus potentially decreasing the risk of TBI-associated dementia [72].…”
Section: Traumatic Brain Injurymentioning
confidence: 98%